2021
DOI: 10.3390/ph14090938
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Syntheses of Both Enantiomers of Plymuthipyranone B and Its Unnatural Analogues: Evaluation of anti-MRSA Activity and Its Chiral Discrimination

Abstract: Chiral total syntheses of both enantiomers of the anti-MRSA active plymuthipyranone B and all of the both enantiomers of three unnatural and synthetic analogues were performed. These two pairs of four chiral compounds are composed of the same 3-acyl-5,6-dihydro-2H-pyran-2-one structure. The starting synthetic step utilized a privileged asymmetric Mukaiyama aldol addition using Ti(OiPr)4/(S)-BINOL or Ti(OiPr)4/(R)-BINOL catalysis to afford the corresponding (R)- and (S)-δ-hydroxy-β-ketoesters, respectively, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Various natural products containing heterocyclic rings have been synthesized by numerous research groups and their evaluation against bacterial, fungal, viral and cancer cell lines has been carried out. In this regard, Moriyama et al 151 in 2021 reported the chiral total synthesis of both enantiomers of naturally occurring polymuthipyranone B by employing the chiral BINOL reagent mediated Mukaiyama aldol reaction as key step. Moreover, they carried out the synthesis of their three synthetic counterparts.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Various natural products containing heterocyclic rings have been synthesized by numerous research groups and their evaluation against bacterial, fungal, viral and cancer cell lines has been carried out. In this regard, Moriyama et al 151 in 2021 reported the chiral total synthesis of both enantiomers of naturally occurring polymuthipyranone B by employing the chiral BINOL reagent mediated Mukaiyama aldol reaction as key step. Moreover, they carried out the synthesis of their three synthetic counterparts.…”
Section: Review Of the Literaturementioning
confidence: 99%